2009
DOI: 10.1371/journal.pgen.1000491
|View full text |Cite
|
Sign up to set email alerts
|

Murine Leukemias with Retroviral Insertions at Lmo2 Are Predictive of the Leukemias Induced in SCID-X1 Patients Following Retroviral Gene Therapy

Abstract: Five X-linked severe combined immunodeficiency patients (SCID-X1) successfully treated with autologous bone marrow stem cells infected ex vivo with an IL2RG-containing retrovirus subsequently developed T-cell leukemia and four contained insertional mutations at LMO2. Genetic evidence also suggests a role for IL2RG in tumor formation, although this remains controversial. Here, we show that the genes and signaling pathways deregulated in murine leukemias with retroviral insertions at Lmo2 are similar to those de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(65 citation statements)
references
References 43 publications
(73 reference statements)
0
64
1
Order By: Relevance
“…Expression profiling of pre-leukaemic and wildtype thymocytes, and human T-ALL samples identified a gene-expression signature containing candidates with known roles in haematopoietic stem cell function, and a bone marrow reconstitution model showed that HHEX/ PRH overexpression recapitulated the oncogenic potential of lmo2. Dave et al (2009) andMcCormack et al (2010) both suggest a possible role of the LMO2-ETS factor interaction and identify HHEX/PRH as a potential downstream collaborator in mice. However, although these studies have identified lmo2, the ETS factors and HHEX/PRH as collaborating oncogenes, they do not distinguish whether they function in a parallel, overlapping or hierarchical manner.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Expression profiling of pre-leukaemic and wildtype thymocytes, and human T-ALL samples identified a gene-expression signature containing candidates with known roles in haematopoietic stem cell function, and a bone marrow reconstitution model showed that HHEX/ PRH overexpression recapitulated the oncogenic potential of lmo2. Dave et al (2009) andMcCormack et al (2010) both suggest a possible role of the LMO2-ETS factor interaction and identify HHEX/PRH as a potential downstream collaborator in mice. However, although these studies have identified lmo2, the ETS factors and HHEX/PRH as collaborating oncogenes, they do not distinguish whether they function in a parallel, overlapping or hierarchical manner.…”
Section: Discussionmentioning
confidence: 98%
“…Recent work from insertional mutagenesis models in mice (Dave et al, 2009) has shown that the genes and signalling pathways deregulated in murine leukaemias with retroviral insertions at LMO2 are analogous to both those dysregulated in highly LMO2-expressing human leukaemias (Ferrando et al, 2002;Yeoh et al, 2002;Chiaretti et al, 2004) and to the LMO2 retroviral insertion-mediated leukaemias induced in severe combined immunodeficiency-X1 patients (Hacein-BeyAbina et al, 2003a, b, 2008. Moreover, many of these genes are components of haematopoietic stem cell transcriptional regulatory networks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20 In support of this hypothesis, several reports have shown a striking correlation between LMO2, TAL1, and Olig2 based on gene expression analysis in human and murine T-cell leukemia. [21][22][23] In future studies, it will be interesting to explore whether LMO2 interacts with Olig2 to regulate GSCs and brain tumorigenesis. Presence of tumor-derived vascular components sheds light on the plasticity of cancer cells and the potential involvement of cancer stem cells in cancer-associated angiogenesis.…”
Section: Discussionmentioning
confidence: 99%